Preparation of a Specific ssDNA Aptamer for Brevetoxin-2 Using SELEX - Rui-Yun Tian; Chao Lin; Shi-Yu Yu; Sheng Gong; Pan Hu; Yan-Song Li; Zong-Cheng Wu; Yang Gao; Yu Zhou; Zeng-Shan Liu; Hong-Lin Ren; Shi-Ying Lu (Journal of Analytical Methods in Chemistry)
The existing assays for detecting brevetoxin (BTX) depend on expensive equipment with a professional operator or on an antibody with limited stability, which requires complex processes, a high cost, and a considerable amount of time. The development of an alternative detection probe is another promising research direction. This paper reports the use of aptamers binding to BTX-2 in an analytical assay using the systematic evolution of ligands by exponential enrichment (SELEX). After 12 rounds of selection, the secondary structures of 25 sequences were predicted. Compared to other aptamers, Bap5 has relatively high affinity with the lowest dissociation constant of 4.83 μM, and IC50 is 73.81 ng mL−1. A good linear regression formula of y=30.688x-7.329 with a coefficient correlation of R2 = 0.9798 was obtained using a biotin-avidin ELISA. Moreover, there is no cross-reaction with the detected marine toxins, except for BTX-2. Thus, Bap5 has potential to detect BTX-2 in shellfish in the future as a substitute for the recognition probe.